Experimental and theoretical studies on the adjustable thermal properties of epoxy composites with silver‐plated short fiberglass. Issue 48 (27th July 2017) - Bao, Rui; Yan, Shilin; Wang, Ruogu; Li, Yongjing
ABSTRACT: This article investigates the evolution of the thermal conductivity and the coefficient of thermal expansion (CTE) of epoxy composites filled with different silver‐plated short glass fibers (Ag@GFs) treated by electroless plating. After electroless plating, the results of X‐ray diffraction and scanning electron microscopy showed that glass fibers were coated with pure silver shells whose thickness was controlled via the repetition of electroless plating cycle, and calculated by weighting method. The optical photographs showed that Ag@GFs are randomly oriented and uniformly dispersed in the composites. HotDisk thermal constant analyzer and dilatometer were used to further characterize the thermal conductivity and the CTE of the composites, respectively. The results revealed that the thermal conductivity of Ag@GF/epoxy composites increased with the increase of Ag@GF content, and was adjusted by changing the thickness of silver shell. But the CTE of the composites drops sharply as the Ag@GF content increases compared with neat epoxy. Based on Agari model with fitted factors of Cp and Cf, the calculated thermal conductivity values of Ag@GF/epoxy composites agreed well with the experimental results, and Cp kept almost unchanged, but Cf varied with the change of the thickness of silver shell, despite increasing filler content. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45555. Abstract :